2017
DOI: 10.23986/afsci.59308
|View full text |Cite
|
Sign up to set email alerts
|

The potential of biochar for reducing the negative effects of soil contamination on the phytochemical properties and heavy metal accumulation in wheat grain

Abstract: The food industry faces the problem of soil contamination and consequently the deterioration of the quality of plant products. Here, we present a study on evaluation of the effect of fertilization with sewage sludge (SL) with varying, rates of biochar (BC 2.5, 5 and 10% of DW) on yield quality and the accumulation of heavy metals in wheat grains. The greatest grain yield with the highest content of protein and gluten as well as the highest total content of phenols and flavonoids, was obtained when SL+5%BC fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, Refs. [50,51] found that the addition of biochar can also impact on phenolic compounds in wheat and in Viola cornuta flowers, respectively. The simultaneous application of NPK and biochar had a positive effect on barley performance under control conditions, while the response of plants varied depending on the salt concentration and the amount of biochar in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Refs. [50,51] found that the addition of biochar can also impact on phenolic compounds in wheat and in Viola cornuta flowers, respectively. The simultaneous application of NPK and biochar had a positive effect on barley performance under control conditions, while the response of plants varied depending on the salt concentration and the amount of biochar in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Plants increase phenolic compounds in stress conditions due to the increase of free radicals so that they can initiate appropriate defense reactions. Some studies have reported an increase in flavonoids due to the use of biochar in plants (Różyło et al, 2017;Hashemi & Shahani, 2019). The increase in flavonoids can be explained by the relative humidity and the amount of nitrogen in the leaves (Yang et al, 2018;Shiwakoti., et al, 2016), and the biochar improves those properties.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar is known to influence the amino acid (phenylalanine) concentration of plants [66], which may affect phenol compound synthesis, as they are the pre-cursor of phenols in the Shikimic acid pathway [65]. Ró żyło et al [67] found that adding biochar with sewage sludge can also impact phenolic and flavonoid concentration in wheat, but no obvious trend was seen in phytochemical concentration. This was similar to findings in this study, where we did not find any significant trend in the change of specific phytochemicals in Viola.…”
Section: Characterization Of Viola Extractsmentioning
confidence: 99%